Kekerasan mikro resin komposit packable dan bulkfill dengan kedalaman kavitas berbeda - Diatri Nari Ratih; Andina Novitasari (Majalah Kedokteran Gigi Indonesia, 2017)
Microhardness of packable and bulkfill composite resin with different cavity depths. Bulkfill composite resin restorations are increasingly popular because the material can be irradiated with a thickness reaching 4 mm, making it easier to apply. The objective of this study was to determine the differences in the microhardness between packable and bulkfill composite resin restorations with a cavity depth of 2 mm and 4 mm. This study was done using 32 Teon molds (5 mm diameter), and grouped randomly into 4 groups in which each consisted of 8 samples. Group 1A, packable composite resin was applied to the mold with a cavity depth of 2 mm. Group 1B, bulkfill composite resin was applied to the mold with a cavity depth of 2 mm. Group 2A, packable composite resin was applied with a depth of 4 mm. Group 2B, bulkfill composite resin was applied with a depth of 4 mm. Each sample was immersed in articial saliva with a pH of 6.8 and stored in an incubator at a temperature of 37°C for 24 hours. The hardness of each sample was tested using Vickers indenter microhardness tester. The data obtained were then analyzed by using two-way ANOVA, followed by Tukey’s test. The results showed that bulkfill composite resin with a cavity depth of 2 mm has the highest average of microhardness (31.09 ± 2.02 VHN), followed by packable composite resin with a depth of 2 mm (17.52 ± 1.25 VHN), bulkfill with a depth of 4 mm (11.97 ± 1.23 VHN) and packable with a depth of 4 mm (3.18 ± 0.85 VHN). The two-way ANOVA analysis showed that there are significant differences between the types of composite resin and cavity depths (p < 0.05), and there is interaction between the types of composite resin and cavity depth (p<0.05). In conclusion, the microhardness of packable composite resin is lower than that of bulkfill at a cavity depth of 2 and 4 mm. ABSTRAKRestorasi resin komposit dengan bulkfill semakin populer karena material tersebut dapat disinar dengan ketebalan sampai 4 mm, sehingga mudah diaplikasikan. Tujuan dari penelitian ini adalah untuk mengetahui perbedaan kekerasan mikro restorasi resin komposit packable dan bulkfill dengan kedalaman kavitas 2 mm dan 4 mm. Penelitian ini dilakukan dengan menggunakan 32 cetakan Teflon (diameter 5 mm), dan dikelompokkan secara random menjadi 4 kelompok yang masing-masing terdiri dari 8 sampel. Kelompok 1A, cetakan diaplikasikan resin komposit packable dengan kedalaman kavitas 2 mm. Kelompok 1B, diaplikasikan komposit bulkfill dengan kedalam 2 mm. Kelompok 2A, diaplikasikan komposit packable dengan kedalaman 4 mm. Kelompok 2B, diaplikasikan komposit bulkfill dengan kedalaman 4 mm. Setiap sampel direndam dalam saliva buatan dengan pH 6,8 dan disimpan dalam inkubator dengan suhu 37 °C selama 24 jam. Setiap sampel diuji kekerasannya menggunakan Vickers indenter microhardness tester. Data yang diperoleh dianalisis dengan ANOVA dua jalur, dilanjutkan uji Tukey’s. Hasil penelitian menunjukkan resin komposit bulkfill dengan kedalaman kavitas 2 mm memiliki rerata kekerasan mikro tertinggi (31,09 ± 2,02 VHN), diikuti oleh resin komposit packable dengan kedalaman 2 mm (17,52 ± 1,25 VHN), bulkfill dengan kedalaman 4 mm (11,97 ± 1,23 VHN) dan packable dengan kedalaman 4 mm (3,18 ± 0,85 VHN). Analisis ANOVA dua jalur menunjukkan bahwa terdapat perbedaan yang signifikan antara jenis resin komposit dan antara kedalaman kavitas (p < 0,05), serta terdapat interaksi antara jenis resin komposit dan kedalaman kavitas (p < 0,05). Kesimpulannya, kekerasan mikro resin komposit packable lebih rendah dibandingkan bulkfill baik pada kedalaman kavitas 2 dan 4 mm.